Ampelopsin Suppresses Stem Cell Properties Accompanied by Attenuation of Oxidative Phosphorylation in Chemo- and Radio-Resistant MDA-MB-231 Breast Cancer Cells - Truong, Vi Nguyen-Phuong; Nguyen, Yen Thi-Kim; Cho, Somi-Kim (Pharmaceuticals (Basel, Switzerland), 2021)
Ampelopsin, also known as dihydromyricetin, is a commonly found flavonoid in medicinal plants. The cancer stem cell (CSC) population is a promising target for triple-negative breast cancer (TNBC). In this study, flavonoid screening was performed in the established MDA-MB-231/IR cell line, which is enriched in CSCs. Ampelopsin suppressed the proliferation and colony formation of stem cell-rich MDA-MB-231/IR, while inducing their apoptosis. Importantly, ampelopsin displayed an inhibitory impact on the stemness features of MDA-MB-231/IR cells, demonstrated by decreases in mammosphere formation, the CD44+/CD24−/low population, aldehyde dehydrogenase activity, and the levels of stem cell markers (e.g., CD44, MRP1, β-catenin, and KLF4). Ampelopsin also suppressed the epithelial–mesenchymal transition, as evidenced by decreases in migration, invasion capacity, and mesenchymal markers, as well as an increase in the epithelial marker E-cadherin. Moreover, ampelopsin significantly impaired oxidative phosphorylation by reducing the oxygen consumption rate and adenosine triphosphate production in MDA-MB-231/IR cells. Notably, ampelopsin treatment significantly reduced the levels of the phosphorylated forms of IκBα and NF-κB p65, as well as the levels of tumor necrosis factor (TNF)-α-stimulated phosphorylation of IκBα and NF-κB p65. These results demonstrated that ampelopsin prevents the TNF-α/NF-κB signaling axis in breast CSCs.